The relationship between public balance and inflation in Europe - Patrícia Miklós-Somogyi; László Balogh (Bamberg University, Bamberg Economic Research Group on Government and Growth (BERG), 2009)
The study considers some of the factors determining budget balance. In particular, it investigates the relationship between budget balance and inflation. The analysis focuses on European states in the period between 1999 and 2007, and concludes that the relationship between budget balance and inflation is not demonstrable. In the literature, attempts to quantify the relationship between the two factors have faced severe difficulties. Inflation influences both the revenue side and the expenditure side of the budget, often increasing one and reducing the other at the same time. These effects might balance each other out, leaving the budget balance unchanged.
Keywords: 330; budget balance; budget deficit; inflation; Öffentlicher Haushalt; Haushaltsdefizit; Inflation; Schätzung; Europa